Direct‐acting antivirals for chronic hepatitis C - Jakobsen, Janus C.; Weiss, Karl Heinz (The Cochrane database of systematic reviews, 2017)
enfresMillions of people worldwide suffer from hepatitis C, which can lead to severe liver disease, liver cancer, and death. Direct‐acting antivirals (DAAs), e.g. sofosbuvir, are relatively new and expensive...enmshrfresDirect‐acting antivirals for chronic hepatitis C Background Millions of people worldwide suffer from hepatitis C, which can lead to severe liver disease, liver cancer, and death. Numerous previous...